Functional characterization of the vitellogenin promoter in the silkworm, Bombyx mori. Issue 5 (15th May 2014) - Xu, J.; Wang, Y. Q.; Li, Z. Q.; Ling, L.; Zeng, B. S.; You, L.; Chen, Y. Z.; Aslam, A. F. M.; Huang, Y. P.; Tan, A. J.
Abstract Genetic transformation and genome editing technologies have been successfully established in the lepidopteran insect model, the domesticated silkworm, Bombyx mori, providing great potential for functional genomics and practical applications. However, the current lack of cis‐regulatory elements in B. mori gene manipulation research limits further exploitation in functional gene analysis. In the present study, we characterized a B. mori endogenous promoter, Bmvgp, which is a 798‐bp DNA sequence adjacent to the 5′‐end of the vitellogenin gene (Bmvg). PiggyBac‐based transgenic analysis shows that Bmvgp precisely directs expression of a reporter gene, enhanced green fluorescent protein (EGFP), in a sex‐, tissue‐ and stage‐specific manner. In transgenic animals, EGFP expression can be detected in the female fat body from larval−pupal ecdysis to the following pupal and adult stage. Furthermore, in vitro and in vivo experiments revealed that EGFP expression can be activated by 20‐hydroxyecdysone, which is consistent with endogenous Bmvg expression. These data indicate that Bmvgp is an effective endogenous cis‐regulatory element in B. mori.